Dilemmas of democratic consolidation : a game-theory approach - Ulfelder, Jay 1969- (FirstForumPress, 2010)
The democracy game -- How fragile is democracy? patterns in cross-national data -- How does democracy break down? evidence from random narratives -- Exploring confounding cases -- Implications for democracy promotion